Sarcomatose transformation in von Recklinghausen’s disease - de Pena, Mario; Carriquiry, Luis A; Davidenko, Nicolás; Peyroulou, Alfredo; Gómez Fossati, Carlos; Priario, Julio César (Cirugía del Uruguay, 1979)
The authors describe 2 clinical observations of neurofibrosarcomas in patients suffering from von Recklinghausen's disease ( or multiple .neurofibromato'sis) : 1 mediastinal fibrosarcoma and 1 neurofibrosarcoma of right femoral nerve. Therc is a bibliographic review of sarcomatose transformation in von Recklinghausen's disease.